Public policy of support for small business innovation in the U.S.: lessons for Russia - E. A. Zinovieva; A. Balyshev (Vestnik MGIMO-Universiteta, 2014)
The article analyzes the characteristics of the program of Assistance to Small Business Innovation Research (SBIR) in the United States. This program is aimed at support and subsequent commercialization of high technology developed by small firms. The government agencies involved in the implementation of the program determine the research areas manage the allocated funds themselves. The program has been in operation for over 30 years and has proven to be effective. It provides business with funds necessary at the primary, the most risky phase of production of innovative goods and services, and also gives signals to the market about popular areas of innovation development. Participation in the program is a guarantee of a high level for innovative product or service produced by the firm and allows companies to raise additional funds. Conclusions drawn from the analysis of the SBIR may be useful for the policy support of science and technology in Russia. The implementation of programs similar to SBIR in Russia will solve the actual problem of innovation development, to reduce information asymmetry in the market of innovative products and services and help in attracting venture capital in high-technology projects.